Московская сага: трилогия / Василий Аксенов ; художник Александр Анно - Аксенов Василий Павлович (Изограф, 2000)
Экземпляры: АБ (20221208) / Инвентарный номер: 34989 / Цена: 85.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: А 42 / ББК: 84(2Рос=Рус)6